Measuring the automatic negative self-schema: New evidence for the construct and criterion validity of the Depression Implicit Association. Issue 5 (2nd September 2016) - Dentale, Francesco; Grano, Caterina; Muzi, Milena; Pompili, Maurizio; Erbuto, Denise; Violani, Cristiano
Abstract: The construct and criterion validity of the Depression Implicit Association Test (Depression IAT) as a marker of an automatic negative self-schema was investigated. The Depression IAT and other measures were administered to a sample of 116 participants (72 females) aged 37.28 (SD = 15.69) that was composed by 56 patients with an history of suicide ideation (SI) and by 60 university students. Combining students and patients' sub-samples, results revealed that the Depression IAT was significantly and positively correlated with self-report scales of depression and hopelessness as well as with implicit and explicit measures of death-life identification. On the contrary, it was negatively correlated with life satisfaction, optimism, and self-esteem scales. These results give new evidence for the construct validity of the Depression IAT. Moreover, considering only the patients' sub-sample, significant correlations between Depression IAT scores and SI in the last year, month, and week, as well as in a follow-up observation two months later, were found. These correlations remain unchanged even when the Death IAT was controlled for, supporting the incremental validity of the Depression IAT. Overall, these results provide new evidence for the construct and criterion validity of the Depression IAT as a marker of an automatic negative self-schema.